The apartment : a novel - Menéndez, Ana, 1970- (Counterpoint, 2023)
"The Helena is an art deco apartment building that has witnessed the changing face of South Miami Beach for seventy years, observing the lives housed within. Among those who have called apartment 2B home across the decades are a Cuban concert pianist who performs in a nursing home; the widow of an intelligence officer raising her young daughter alone; a man waiting on a green card marriage to run its course so that he can divorce his wife and marry his lover, all of whom live together; a Tajik building manager with a secret identity; and a troubled young refugee named Lenin. Each tenant imbues 2B with energy that will either heal or overwhelm its latest resident, Lana, a mysterious woman struggling with her own past"--